B31 Sirt1 expression, regulation and activity in R6/2 mice. (13th September 2016) - Nørremølle, Anne; Reynolds, Regina; Petersen, Maria; Willert, Cecilie; Heinrich, Marie; Nymann, Nynne; Dall, Morten; Treebak, Jonas T; Björkqvist, Maria; Hasholt, Lis
Abstract : Background: Sirtuin 1 (SIRT1) is an NAD+-dependent deacetylase, with a key role in the regulation of numerous metabolic pathways. Of special relevance to Huntington's disease (HD), SIRT1 deacetylates and activates peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α). Furthermore, SIRT1 acts as a positive regulator of brain-derived neurotrophic factor (BDNF) expression through stimulation of the CREB-TORC1 transcription factor complex. Both PGC-1α activity and BDNF expression are reduced in HD models, indicating inhibition of SIRT1 activity in HD. Indeed, Tulino et al. (2016) observed reduced SIRT1 activity with unchanged protein levels in neuronal nuclei from transgenic HD mice (R6/2). SIRT1 expression is regulated by the microRNA miR-34a and by a long non-coding antisense RNA (SIRT1 AS lncRNA). SIRT1 activity is regulated by NAD+ availability, which is in part controlled by the activity of the NAD+ salvage pathway, where nicotinamide phosphoribosyltransferase (NAMPT) is the rate-limiting enzyme. Aim: To determine whether SIRT1 expression and activity is dysregulated in whole brain extracts from R6/2 mice near disease onset and in late-stage HD. We assessed expression of SIRT1 protein, Sirt1 mRNA, miR-34a and SIRT1 AS lncRNA. In addition, we measured the NAD+ and NAMPT levels, and the activity of SIRT1, in late-stage mice. Results: We found significant or strong tendencies to decreased miR-34a expression, increased levels of Sirt1 mRNA and protein, and similar levels of SIRT1 AS lncRNA, NAD+, NAMPT and SIRT1 activity in R6/2 mice compared to wild type mice. Conclusion: Our results indicate that an up-regulation of SIRT1 protein takes place during HD progression, but that this does not lead to increased SIRT1 activity.